RELASI MANUSIA DAN ALAM DALAM AL- QUR’AN (Studi Komparatif Tafsir Fi Zilal Al- Qur’an dan Tafsir Al- Azhar Surah Hud ayat 61 dan Al- A’raf ayat 56) - Nuvi Fitriyani; Moh. Jufriyadi Sholeh (AL-BAYAN INSTITUTE, 2023)
As God's creation, humans are given privileges that make them different from other creatures, because of this privilege humans are appointed as leaders on earth. To carry out this leadership role, humans need support from the universe and everything in it. Humans actively act on nature by utilizing and modifying it. In contrast, nature passively provides resources and only responds to human treatment without initiative or will. This relationship requires humans to be responsible for maintaining balance so that nature remains sustainable and supports life. This research examines the relationship between humans and nature in Surah Hud verse 61 and Al-A'raf verse 56, with a focus on the interpretation of Sayyid Qutb and Buya Hamka. The research method used is documentation by comparing the two interpretations (muqaran). The results of the research show that there are similarities in the interpretation of the two mufasir in Surah Hud verse 61 that humans were created from earth, whereas in Surah Al-A'raf verse 56 the two mufasir have differences in their interpretation. Sayyid Quthb interprets natural damage from a material perspective which is caused by excessive desires in managing nature, while Buya Hamka interprets damage from two angles, namely material damage and mental damage which can cause natural damage